Structural requirements for voltage-dependent block of muscle sodium channels by phenol derivatives. - Haeseler, G; Piepenbrink, A; Bufler, J; Dengler, R; Aronson, J; Piepenbrock, S; Leuwer, M (2001)
We have studied the effects of four different phenol derivatives, with methyl and halogen substituents, on heterologously expressed human skeletal muscle sodium channels, in order to find structural determinants of blocking potency. All compounds blocked skeletal muscle sodium channels in a concentration-dependent manner. The methylated phenol 3-methylphenol and the halogenated phenol 4-chlorophenol blocked sodium currents on depolarization from -100 mV to 0 mV with IC(50) values of 2161 and 666 microM respectively. Methylation of the halogenated compound further increased potency, reducing the IC(50) to 268 microM in 2-methyl-4-chlorophenol and to 150 microM in 3,5-dimethyl-4-chlorophenol. Membrane depolarization before the test depolarization increased sodium channel blockade. When depolarizations were started from -70 mV or when a 2.5 s prepulse was introduced before the test pulse inducing slow inactivation, the IC(50) was reduced more than 3 fold in all compounds. The values of K(D) for the fast-inactivated state derived from drug-induced shifts in steady-state availability curves were 14 microM for 3,5-dimethyl-4-chlorophenol, 19 microM for 2-methyl-4-chlorophenol, 26 microM for 4-chlorophenol and 115 microM for 3-methylphenol. All compounds accelerated the current decay during depolarization and slowed recovery from fast inactivation. No relevant frequency-dependent block after depolarizing pulses applied at 10, 50 and 100 Hz was detected for any of the compounds. All the phenol derivatives that we examined are effective blockers of skeletal muscle sodium channels, especially in conditions that are associated with membrane depolarization. Blocking potency is increased by halogenation and by methylation with increasing numbers of methyl groups.